Russia-India relations in the post cold war era the China factor - Singh, Ajay K. (Ajay Kumar) (KW Publishers, 2016)
This monograph explains how historical legacy has created mistrust in Russia-China and India-China relations. In the case of Russia-India relations, it has played a positive role in deepening their relationship in the post Cold War era. Also the geographical contiguity of Russia and India with China has provided a constant factor to collaborate India and Russia for sustainable peace in Asia. This monograph also examines the China factor in Russia-India relations in the context of today's multi-polar world and in the context of multilateral engagements which throws many challenges and opportunities for India.